Primary Localized Amyloidosis of the Bladder Mimicking Neoplasia - Sümeyye Ekmekçi (Journal of Urological Surgery, 2018)
A 63-year-old woman was admitted to our hospital with macroscopic hematuria in 2013. On computed tomography, the bladder wall thickness was 2 cm, suspicious for malignancy. Cystoscopy showed irregularity in the posterolateral side of the bladder. Transurethral resection was performed. Histopathological examination revealed a dense homogeneous eosinophilic material in the lamina propria which showed positive orange-red staining with apple-green birefringence under polarized light. There were no signs of systemic amyloidosis at the time of diagnosis and during the 36 months of follow-up. Differential diagnosis of amyloidosis in the bladder includes urothelial carcinoma due to its appearance on imaging and cystoscopy. Histopathological evaluation is a requirement for accurate diagnosis.